Electronic structures and enhanced photocatalytic properties of blue phosphorene/BSe van der Waals heterostructures. Issue 19 (12th April 2018) - Wang, Bao-Ji; Li, Xiao-Hua; Zhao, Ruiqi; Cai, Xiao-Lin; Yu, Wei-Yang; Li, Wei-Bin; Liu, Zhen-Shen; Zhang, Li-Wei; Ke, San-Huang
Abstract : Constructing van der Waals heterostructures can enhance two-dimensional (2D) materials with desired properties and greatly extend the applications of the original materials. Abstract : Constructing van der Waals heterostructures can enhance two-dimensional (2D) materials with desired properties and greatly extend the applications of the original materials. On the basis of density functional theory calculations, we verify that a blue phosphorene (BlueP)/BSe inter-layer heterostructure possesses an indirect gap and intrinsic type-II band alignment. In particular, this heterostructure is found to be a potential photocatalyst for water splitting under different pH conditions and exhibits enhanced optical properties in the visible and ultraviolet light zones. Besides, we confirm that the band gap, band edge position, and optical absorption of the BlueP/BSe heterostructure can be tailored by biaxial strain. And the tensile strain increases the optical absorption significantly over the entire energy range of visible light, which can increase the efficiency of solar energy conversion. Furthermore, we determine that adjusting the number of sublayers is another effective method to modulate the band gaps and band alignments of heterostructures. Our studies provide a promising route to design new BlueP-based vdW heterostructures and explore their potential applications in electronic and optoelectronic devices.